Are microorganisms indispensable in green microbial nanomaterial synthesis? - Liu, Lihong; Shao, Zongping; Ang, Ming; Tade, Moses; Liu, Shaomin (Royal Society of Chemistry, 2014)
Typical microbial synthesis relies heavily on microbial alchemy. In this work, we demonstrate a conceptually new, greener strategy using aqueous microbial culture broths alone for nanosynthesis by eliminating the complication of manipulating genetically engineered microbes and maintaining the cell cultures. This versatile method is exemplified by the preparation of gold nanoparticles and reduced graphene oxide.